2008
DOI: 10.1007/s10764-008-9234-0
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Ecology of Trachypithecus pileatus in India

Abstract: We observed a group of capped langurs for 12 mo in the Pakhui Wildlife Sanctuary, Arunachal Pradesh, India. We recorded the time of feeding on different food plant species, food categories, and the feeding heights of monkeys in trees. Capped langurs spent 68% of their feeding time on leaves, 16% on flowers, and 16% on fruits. Feeding on leaves was consistently high (p<0.01) during the year, with the highest feeding in May (85%) and the lowest in January (47%). The seasonal difference in feeding on leaves is si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…The three study species consumed fruits mostly in the wet season, although the consumption of some fruit items by lion-tailed macaques was highly seasonal, irrespective of their availability. It has been reported earlier, however, that, unlike Hanuman langurs, some other colobine monkeys, such as capped langurs, consumed flowers as much as fruits [Solanki et al, 2008]. During the post-monsoon season, flowers were a major resource for lion-tailed macaques and bonnet macaques in other parts of the Western Ghats also [Ganesh and Davidar, 1997;Sushma, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…The three study species consumed fruits mostly in the wet season, although the consumption of some fruit items by lion-tailed macaques was highly seasonal, irrespective of their availability. It has been reported earlier, however, that, unlike Hanuman langurs, some other colobine monkeys, such as capped langurs, consumed flowers as much as fruits [Solanki et al, 2008]. During the post-monsoon season, flowers were a major resource for lion-tailed macaques and bonnet macaques in other parts of the Western Ghats also [Ganesh and Davidar, 1997;Sushma, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…Barring the predominantly terrestrial stump-tailed and rhesus macaques, all the primates are mostly arboreal, with the hoolock gibbon being entirely so. The capped langur is mainly folivorous (Solanki et al 2008), whereas the remaining species are primarily frugivorous (Roonwal & Mohnot 1977). Insects and roots, however, constitute a significant part of pigtailed and stump-tailed macaque diets, respectively (N.S., personal observation).…”
Section: Study Areamentioning
confidence: 99%
“…Previous studies also have shown that Asian colobines spend larger proportions of time resting (Stanford 1991;Davies and Oates 1994;Huang et al 2003;Li and Rogers 2004;Zhou et al 2007). For example, the white-headed langurs (Trachypithecus leucocephalus) and capped langurs (T. pileatus) spent 50% and 53% of their day resting, respectively (Li et al 2003;Solanki et al 2008). The activity patterns of primates can be affected by the seasonal changes in food availability (Oates 1987).…”
Section: Discussionmentioning
confidence: 98%